THE INFLUENCE OF CAREER DEVELOPMENT AND WORK CLIMATE ON EMPLOYEE PERFORMANCE AT PT SUMBER BANGUNAN CIPTA SEJAHTERA BANTEN - Muhamad Ridwan (JURNAL ASIK, 2025)
This study aims to analyze the influence of career development and work climate on employee performance at PT Sumber Bangunan Cipta Sejahtera Banten. The type of research used is quantitative with a descriptive and verification approach. The research sample of 108 permanent employees was selected using purposive sampling techniques. Data were collected through questionnaires that had been tested for validity and reliability, then analyzed using multiple linear regression. The results of the study showed that career development had a positive and significant effect on employee performance (β = 0.412, p <0.05). Work climate also had a positive and significant effect on employee performance (β = 0.357, p <0.05). Simultaneously, career development and work climate contributed 65.9% in explaining variations in employee performance. These findings indicate that improving career development programs and creating a conducive work climate are effective strategies to improve employee performance in the company. Therefore, companies are advised to continue to develop both aspects so that organizational goals can be achieved optimally Non-formal education is a strategic solution to bridge the gap in education in areas with limited access, including Cianjur Regency. Community Learning Activity Centers (PKBM) as non-formal educational institutions have a central role in providing equal education services, literacy, life skills, and community empowerment. This study aims to analyze the contribution of PKBM to improving the quality of non-formal education in Cianjur, as well as identifying supporting and inhibiting factors in its implementation. The research method used is a qualitative approach with case studies on several PKBM in the Cianjur area. The results of the study indicate that PKBM plays a role in reducing school dropout rates, improving the skills of students, and expanding access to education. However, challenges such as limited funds, educators, and community participation are still major obstacles. This study recommends strengthening synergy between stakeholders and increasing the institutional capacity of PKBM for the sustainability of non-formal education programs